THE RELANTIONSHIP BETWEEN DEPRESSION LEVELS AND QUALITY OF LIFE IN TUBERCULOSIS (TB) PATIENTS AT THE PULMONARY POLYCLINIC OF PAKUHAJI HOSPITAL TANGERANG REGENCY - Nurul Mutmainnah Imran; Osep Yasier Almunsiri; Alif Nurul Rosyidah (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Background: Tuberculosis is a lung infection known as TB. Prolonged treatment of tuberculosis often causes tuberculosis patients stress or depression. Poor psychological conditions can reduce the motivation of patients to undergo long and complex treatment. Objective: To determine the relationship between the level of depression and the quality of life of tuberculosis (TB) patients at Pakuhaji Hospital, Tangerang Regency. Method: The method used in this study is quantitative with a correlational analytical design. The sampling method in this study is by accidental sampling. The sample used in this study was 87 respondents. The instruments used in this study were the standard questionnaire Zung Self-rating Depresssion Scale (ZSDS) and the World Health Organization Quality Of Life- BREF (WHOQOL-BREF). Results: The results of the chi-square test were obtained with a P Value of 0.001 < from a significant value (α = 0.05). Conclusion: The results of this study show that there is a relationship between the level of depression and the quality of life of people with tuberculosis (TB).